ANALISIS PERSEPSI SISWA KELAS X TKR TERHADAP PENGGUNAAN GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN PADA MATA PELAJARAN DASAR-DASAR OTOMOTIF DI SMKN 8 PADANG - Hakim, Bambang Nur; Andrizal, Andrizal; Maksum, Hasan; Fernandez, Donny (Ensiklopedia of Journal, 2025)
Abstract: The digital age has created a fascinating educational paradox. Amidst a tsunami of technology promising interactive learning, SMK Negeri 8 Padang remains shackled to stagnant, old-fashioned lecture methods. However, is the digital generation truly ready to leave their conventional comfort zone This descriptive quantitative study challenges assumptions through an in-depth examination of students in the Automotive Fundamentals program at SMKN 8 Padang. Surprisingly, the students demonstrated high digital literacy in using Google Classroom, while also showing extraordinary enthusiasm for the platform. The most shocking revelation is that Google Classroom is not merely a tool but a catalyst for educational transformation. Students view it as a bridge to a modern approach capable of revolutionizing the conventional system into an open, technology-centric learning ecosystem. This study exposes the blueprint for vocational education transformation that will reshape the future of learning in Indonesia.Keywords:  Learning Media, Google Classroom, Perception, Automotive Basics.